2020
DOI: 10.1097/sla.0000000000003835
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Complications After Pancreatoduodenectomy on Mortality, Organ Failure, Hospital Stay, and Readmission

Abstract: Objective: To quantify the impact of individual complications on mortality, organ failure, hospital stay, and readmission after pancreatoduodenectomy. Summary of Background Data: An initial complication may provoke a sequence of adverse events potentially leading to mortality after pancreatoduodenectomy. This study was conducted to aid prioritization of quality improvement initiatives.Methods: Data from consecutive patients undergoing pancreatoduodenectomy (2014-2017) were extracted from the Dutch Pancreatic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 54 publications
1
33
0
1
Order By: Relevance
“…Despite major developments in surgical technique and perioperative management, rates of POPF and PPH remain a constant and unsolved problem after PD and represent the most relevant triggers of mortality (1)(2)(3)(4)(5). After its introduction in 1942 by Rockey, TP was advocated by some pioneers of pancreatic surgery as prophylaxis of POPF and its associated morbidity and mortality, but abandoned later due to the lack of oncologic benefit and the detrimental effects of apancreatic state (7-10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite major developments in surgical technique and perioperative management, rates of POPF and PPH remain a constant and unsolved problem after PD and represent the most relevant triggers of mortality (1)(2)(3)(4)(5). After its introduction in 1942 by Rockey, TP was advocated by some pioneers of pancreatic surgery as prophylaxis of POPF and its associated morbidity and mortality, but abandoned later due to the lack of oncologic benefit and the detrimental effects of apancreatic state (7-10).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction after pancreaticoduodenectomy (PD) in the presence of soft pancreatic remnant and small-sized pancreatic duct is a challenge even to the experienced pancreatic surgeon. These features are recognized as major risk factors for postoperative pancreatic fistula (POPF), which itself remains the most relevant source of morbidity after PD (1,2). Rates of clinically relevant POPF are well above 20% at high-volume centers, reaching even 40% in the subgroup of patients with high-risk pancreatic remnant (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, POPF occurrence was associated with statistically significant increased rates of postoperative bleeding requiring re-laparotomy (P=0.029), anastomotic leak (P=0.002), 90-day mortality (P=0.036) and prolonged hospital stay (P<0.001). It is widely accepted that a POPF can lead to other serious complications such as bleeding, intra-abdominal sepsis, and anastomotic leak, which are all associated with prolonged hospital stays [ 16 17 49 64 ] and increased mortality rates [ 66 67 ]. Enzymatic, local septic vascular, or visceral erosions in the setting of POPF formation might explain the increased rates of late hemorrhage and anastomotic leak.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] A recent nationwide study demonstrated that when the focus is to reduce length of stay, DGE should be prioritized as this complication may hamper clinical improvement for several weeks. 11 In addition to the economic impact, DGE also has a considerable clinical impact. Patients with DGE are unable to tolerate solid food and experience vomiting and/or gastric distension requiring prolonged nasogastric drainage, nasoenteral tube feeding or even parenteral feeding.…”
Section: Introductionmentioning
confidence: 99%